Coke oven charging system - Quanci, John Francis; Sparling, Danny Edward; Choi, Chun Wai; Mounts, Dexter Junior; Ball, Mark Anthony (2017)
The present technology is generally directed to coal charging systems used with coke ovens. In some embodiments, a coal charging system includes a charging head having opposing wings that extend outwardly from the charging head, leaving an open pathway through which coal may be directed toward side edges of the coal bed. In other embodiments, an extrusion plate is positioned on a rearward face of the charging head and oriented to engage and compress coal as the coal is charged along a length of the coking oven. In other embodiments, charging plates extend outwardly from inward faces of opposing wings.